A Systematic Review of the Efficacy of Community-based, Leisure/Social Activity Programmes for People with Traumatic Brain Injury. Issue 3 (23rd February 2015) - Tate, Robyn; Wakim, Donna; Genders, Michelle
<x content-type="archive" xml:space="preserve">Abstract</x> Background: Many people who have a severe traumatic brain injury (TBI) are not able to resume employment and consequently experience profound changes in their lifestyle. They have increased amounts of 'spare time' yet often find it difficult to engage in meaningful activity. Leisure activities are one way in which meaningful activity can be increased. Aims: This systematic review has two purposes: first, to identify and evaluate the efficacy of community-based interventions for leisure/social activity after TBI, and second to provide details on the types of intervention. Method: Systematic searches were conducted of Medline, PsycINFO and PsycBITE to October 2014, as well as hand searches of two occupational therapy journals. Inclusion criteria were as follows: peer reviewed journal articles on adults with TBI who had participated in a trial evaluating a community-based intervention specifically targeting leisure/social activity. All research methodologies using primary studies that provided empirical, quantitative data were considered. Scientific quality of the studies was evaluated using the PEDro Scale for controlled trials and the Risk of Bias in N-of-1 Trials Scale for single-case designs. Results: Two independent raters screened 196 abstracts, resulting in nine articles that met selection criteria. Data were then independently extracted by the raters. Four of the nine studies used a control condition in their research design (two randomised controlled trials, one controlled but non-randomised study, and one single-case experiment using a changing criterion design). Two of the studies conducted between-group analyses with significant treatment effects for mood and quality of life using active leisure programmes (Tai Chi Qigong and a combined programme of outdoor adventure experiences and goal setting respectively). Intervention programmes identified in the review were then grouped and described according to the approach or model used, including active leisure programmes, social peer mentoring, individual brokered leisure services and a therapeutic recreation model. Additional intervention models and approaches that did not result directly from the systematic review were also described because they provide information on the current approaches used in practice (Clubhouse model and leisure education programmes in the stroke population). Conclusions: There is some evidence for the effectiveness of community-based interventions for leisure/social activity for people who have had a TBI to improve mood and quality of life. The conclusions of this review are that the interventions for this area need to be planned and specific, structured and goal-driven, intensive and conducted over a period of months.